Control, Communication, and the Voice of the Leader. A ControlCharacter Analysis of the 2016 US Presidential Debate - Márton Demeter (KOME: An International Journal of Pure Communication Inquiry, 2017)
In the current research, we showed the strongest parts and the clouds of the speeches of the 2016 presidential candidates Donald Trump and Hillary Clinton. A communication control analysis of this type could reveal the role control-characters play in assessing the performance of the actors of political communication. We also concluded that people want to be controlled in an easy but still total way. To make people think that there is a man who is able to do this: it was Donald Trump’s greatest asset. He was able to utter up to 37% more assertions than his opponent, clearly stressed the boundaries between ‘Us’ and ‘They’, and showed greater integrative complexity and objective control. As the result of our peculiar and detailed linguistic analyses, control direction and thematic role tests show that Trump was a man of ‘know’, ‘say’ and ‘take’, while Clinton was full of ‘think’ and ‘want.’